Multibody Mechatronic Systems Proceedings of the MUSME Conference held in Florianópolis, Brazil, October 24-28, 2017 - Carvalho, João Carlos Mendes; Martins, Daniel; Simoni, Roberto; Simas, Henrique; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
These are the Proceedings of the 6th International Symposium on Multibody Systems and Mechatronics (MUSME 2017) which was held in Florianópolis, Brazil, October 24-28, 2017.  Topics addressed include analysis and synthesis of mechanisms; dynamics of multibody systems; design algorithms for mechatronic systems; simulation procedures and results; prototypes and their performance; robots and micromachines; experimental validations; theory of mechatronic simulation; mechatronic systems; and control of mechatronic systems. The MUSME 2017 Symposium was one of the activities of the FEIbIM Commission for Mechatronics and IFToMM technical Committees for Multibody Dynamics, Robotics and Mechatronics.
Ivvan Valdez, Giuseppe Carbone, Marco Ceccarelli -- Kinematic analysis of an exoskeleton-based robot for elbow and wrist rehabilitation, by Nicolae Plitea, Bogdan Gherman, Giuseppe Carbone, Marco Ceccarelli, Calin Vaida, Alexandru Banica, Doina Pisla, Adrian Pisla -- Experimental Evaluation of Artificial Human Ribs, by Luis Antonio Aguilar, Marco Ceccarelli, Christopher-René Torres-San-Miguel, Guillermo Urriolagoitia-Sosa, Guillermo Urriolagoitia-Calderón -- Kinetostatic model of the human knee for preoperative planning: part A Method and Validation, by Daniel Ponce, Leonardo Mejia Rincon, Ernesto Ponce, Daniel Martins, Rodrigo Roesler, Julio Feller Golin -- Kinetostatic model of the human knee for preoperative planning: part B Clinical application for medical decision making, by Daniel Ponce, Julio Feller Golin, Ernesto Ponce, Rodrigo Roesler, Daniel Martins, Leonardo Mejia Rincon -- On the Kinematics of an Innovative Spherical Parallel Robot for the Shoulder Rehabilitation, by Nicolae Plitea, Calin Vaida, Giuseppe Carbone, Adrian PISLA, Ionut Ulinici, Doina Pisla -- Automatic Elevation System of a Wheelchair, by Sergio Araki, Pamela Florentino, Eduardo Bock, Miichele Saito, Mariana Hernandes, Luciano Fuentes, Isac Fujita, Rodrigo Stoeterau, Daniel Martins,Celso Arruda -- An Initial Assessment of Mechanisms for the Development of New Hospital Beds, by Rodrigo Barreto, Roberto Simoni, Daniel Martins -- Vehicle Dynamics -- Rollover of long combination vehicles: effect of overweight, by Gonzalo Moreno, Vangelo Manenti, Lauro Nicolazzi, Rodrigo de Souza Vieira, Daniel Martins -- Development of a robust integrated control system to improve the stability of road vehicles, by Abel Arrieta Castro, Georg Rill, Hans Ingo Weber -- Powertrain Optimization to Improve Vehicle Performance and Fuel Consumption, by Jony Eckert, Fernanda Correa, Elvis Bertoti, Rodrigo Yamashita, Ludmila Silva, Franco Giuseppe Dedini -- Design and analysis of a wheel with flexible spokes, by Shuaisong Hou, Jingshan Zhao -- Multibody model of a small tire test bench, by Fabio Mazzariol Santiciolli, Ludmila Silva, Elvis Bertoti, Jony Eckert, Rodrigo Yamashita, Franco Giuseppe Dedini -- Maneuverability study of a vehicle with rear wheel steering, by Jhino Silva, Lincol Vargas, Josue Liberato, Junior Quispe, Carlos Munares -- Author Index.  .
Keywords: Mechatronics; Multibody systems; Vibration; Mechanics, Applied; Machinery; Biomedical engineering; Mathematics -- Data processing; Mechatronics; Multibody Systems and Mechanical Vibrations; Machinery and Machine Elements; Biomedical Engineering and Bioengineering; Computational Science and Engineering